Left Atrial 4-Dimensional Flow Magnetic Resonance Imaging: Stasis and Velocity Mapping in Patients With Atrial Fibrillation. Issue 3 (March 2016) - Markl, Michael; Lee, Daniel C.; Ng, Jason; Carr, Maria; Carr, James; Goldberger, Jeffrey J.
Abstract : Objectives: Left atrial (LA) 4-dimensional flow magnetic resonance imaging (MRI) was used to derive anatomic maps of LA stasis, peak velocity, and time-to-peak (TTP) velocity in patients with atrial fibrillation (AF) and to identify relationships between LA flow with LA volume and patient characteristics. Materials and Methods: Four-dimensional flow MRI for the in vivo assessment of time-resolved 3-dimensional LA blood flow velocities was performed in 111 subjects: 42 patients with a history of AF and in sinus rhythm (AF-sinus), 39 patients with persistent AF (AF-afib), 10 young healthy volunteers (HVs), and 20 age-appropriate controls (CTRL). Data analysis included the 3-dimensional segmentation of the LA and the calculation of LA stasis, peak velocity, and TTP maps. Regional LA flow dynamics were quantified by calculating mean stasis, peak velocity, and TTP in the LA center region and the region adjacent to the LA wall. Results: A sensitivity analysis identified thresholds for global LA stasis (<0.1 m/s) and peak velocity (top 5% LA velocities), which detected significant differences between AF patients and controls for global LA stasis (HV, 25% ± 5%; CTRL, 29% ± 10%; AF-sinus, 41% ± 13%; AF-afib, 52% ± 17%) and peak velocity (HV, 0.43 ± 0.02 m/s; CTRL, 0.37 ± 0.04 m/s; AF-sinus, 0.33 ± 0.05 m/s; AF-afib, 0.30 ± 0.05 m/s). Regional analysis revealed significantly increased stasis at both LA center and wall for AF patients compared with age-appropriate controls (29%–84% difference, P < 0.006) and for AF-afib versus AF-sinus patients (22%–30% difference, P < 0.004). In addition, stasis close to the LA wall was significantly elevated ( P < 0.001) compared with the LA center for all subject groups. Multiple regressions revealed significant ( R 2 Adj = 0.45–0.50, P < 0.001) relationships between impaired global LA flow (reduced velocity and increased stasis) with age (|β| = 0.27–0.50, P < 0.002) and LA volume (|β| = 0.26–0.50, P < 0.003). Conclusions: Atrial 4-dimensional flow MRI detected changes in global and regional LA flow dynamics associated with AF, age, and LA volume. Longitudinal studies are needed to test the diagnostic value of LA flow metrics as potential risk factors for thromboembolic events.